What does it take for students to value grades for oral participation? Transparency is key - Westphal, Andrea; Hoferichter, Clara Josepha; Vock, Miriam (Frontiers in Education, 2025)
IntroductionThis study addresses the controversy over whether students consider grades accurate indicators of achievement. We focused on grades for oral participation, as teachers rely on informal assessments in assigning these grades, and educational measurement studies have questioned the validity of such assessments.MethodsBased on two samples of university students (Sample 1: M = 22 years, 80% female; Sample 2: M = 21 years, 67% female) (Total N = 431), we measured whether students perceive grades for oral participation as being reliable indicators of their school achievement. We investigated variations in students’ retrospective perceptions of oral participation grades in different school subjects. We also examined how students’ retrospective perceptions of oral participation grades were linked to grading transparency and student achievement.ResultsOur findings indicate that students perceive oral participation grades as more accurate indicators of their achievement in languages than in mathematics. Oral participation grades were perceived as being more accurate indicators of student achievement by male students and students who reported greater transparency in the assignment of their grades. In mathematics, higher-achieving students perceived grades as being less valid indicators of their achievement.DiscussionOur results imply that teachers should be mindful of transparency when assigning grades for oral participation. By increasing the transparency of their grading, for instance, by telling students in advance what aspects they factor into their grading, teachers can help students view grades for oral participation as valid indicators of their achievement and increase procedural and distributive justice.